VAMOS program: instruments for measuring physical activity, feeding and anthropometry - Mônica Costa Silva; Cezar Grontowski Ribeiro; Tânia Rosane Bertoldo Benedetti (Universidade Federal de Santa Catarina, 2020)
The aim of this study was to indicate instruments to measure the effectiveness of the Active Life Improving Health Program - VAMOS, in physical activity (PA), feeding and anthropometry. Fifty-six participants were selected to act as analysts in the different stages of the work: 1) systematic review, 2) consensus groups, 3) analysis of selected instruments, 4) focus group. Physical activity, feeding and anthropometry measures, considering their applicability, viability and low cost, were selected to be applied in the VAMOS program in Basic Health Units (UBS). Step 1: Systematic literature review selected the instruments most used to evaluate PA, feeding and anthropometry, organizing a matrix based on established criteria. Step 2: consensus groups performed the choice of the main instruments in the matrix, excluding the two less viable. Step 3: Experts from the five regions of Brazil selected the main instruments included in the matrix, excluding the two least viable ones. Step 4: The focus group established the instruments that were most feasible for use in UBS. The instruments selected to verify effectiveness in physical activity were IPAQ short-version and pedometer for feeding the VIGITEL questionnaire, for anthropometric variables body mass, height, waist circumference and body mass index. The technical and scientific process carried out allows inferring that the VAMOS program should use the above mentioned instruments to measure effectiveness within criteria of applicability, viability and low-cost.